SOSIALISASI PENANAMAN KARAKTER SALING MENGHARGAI MELALUI DUTA ANTI BULLYING UNTUK SISWA DI SEKOLAH DASAR - Bramantha, Heldie; Syarifa, Mufarrahatus (PARADIGMA PENGABDIAN, 2024)
This activity aims to provide a new understanding of social patterns that have been prevalent in the middle of elementary students. Through the elected and trained “duta anti bullying", it is hoped that they can help friends around them realize that scolding others, until they are angry and cry hysterically, and disturbing others, until they are in fight, is a bullying and will have a negative impact on the victims. After socializing bullying to ambassadors and companion teachers, it appears that the ambassadors began to introduce bullying to their friends. They make bullying as a topic of conversation during break times.